Wpływy europejskie na drodze do odrodzenia narodowego Turków - Skowron, Emilia (Humaniora. Czasopismo Internetowe, 2022)
The Turkish Republic, unlike the Ottoman Empire, became a state of one nation, the Turks. The process of changes, the aim of which was to preserve the country’s sovereignty was aiming for the modernization and Europeanization of the country. The weakened Ottoman state required restoration, so the need for changes was noticed very early, using the achievements of Europeans. During the transformation of the state, reforms of Mustafa Kemal Atatürk turned out to be crucial, as he fully achieved what in previous centuries was only in the phase of deliberation or partial implementation. The article analyzes the process of changes that took place from the crisis of the Ottoman Empire to the first years of the Turkish Republic, focusing mainly on the reforms implemented by Atatürk. For the whole picture of changes, it is important to recall the ideas and trends that inspired him to undertake such actions.